Design and Analysis of Ultralow Voltage Graphene on the Silicon Rich Nitride Tunable Ring Resonator-Based Add-Drop Filter for DWDM Systems - Filston Rukerandanga; Stephen Musyoki; Edwin O. Ataro (International Journal of Optics)
We propose and simulate a third-order 3D electro-optically highly tunable compact add-drop filter based on nonlinear microring resonators. The used tuning mechanism relies on enhanced Kerr nonlinearity in a graphene layer integrated on top of a two-photonabsorption-free and low loss silicon-rich nitride core material at telecommunication wavelengths. An ultrahigh tuning efficiency (150 pm/V) over a tuning range of 1.3 nm, ensuring ultralow voltage consumption, was achieved in this work. We used titanium oxide and silicon oxide as the upper-cladding and under-cladding materials, respectively, around the silicon-rich nitride core material, to come up with a polarization-insensitive, and the thermally resilient third-orderadd-drop optical filter in the L band (1565 nm–1625 nm) with a full wave at a half maximum bandwidth of 50 GHz (linewidth of 0.4 nm) around 1570 nm, a high-free spectral range of 18.5 nm, a quality factor of 2580, an extinction ratio of 60 dB, a finesse of 19, and a thermal stability of 0.3 pm/K. A three-dimensional multiphysics approach was used to simulate the propagation of transverse electric and transverse magnetic polarized waves through the filter, combining the electromagnetic features with thermo-optic and stress-optical effects. The contribution of this work to the existing literature is that the designed filter proposes a new and highly tunable material system compatible with the complementary metal-oxide-semiconductor fabrication technology while combining high tunability, polarization insensitivity, and high thermal stability features for an ultracompact and energy-efficienton-chip integrated photonic tunable filter for dense wavelength division multiplexing systems in the less occupied L band.